The Influence of STEM-based Physics Module to Enhance Critical Thinking Skills - Damayanti, Eka Diah; Suwarma, Irma Rahma; Muslim, Muslim (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2023)
One effective way of training 21st-century skills, such as critical thinking, is by utilizing the STEM approach to learning. This study aimed to investigate the influence of STEM-based physics modules on the critical thinking skills of 11th-grade students. For this study, the quantitative research method was employed with the research design of a one-group pre-test post-test design. The data was collected from 33 students in a high school in Sukabumi, Indonesia. The researchers developed a module based on STEM principles focused on sound waves, which was then delivered to the students. They were given a pre-test and post-test of five essay questions to assess the student’s critical thinking skills. Each question measures each critical thinking skill aspect : elementary clarification, basic support, inference, advanced clarification, and supposition and integration. After analyzing the pre-test and post-test results of the students, Normalized gain calculations were used to measure improvement. The research indicated that the N-gain for the student’s critical thinking skills was 0.58, placing it in the medium enhancement category. As a result, it can be concluded that the STEM-based physics module improved the students’ critical thinking skills.